2016
DOI: 10.1007/s40620-016-0364-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral anticoagulant therapy on mortality in end-stage renal disease patients with atrial fibrillation: a prospective study

Abstract: In haemodialysis patients with AF, continuously taking warfarin is associated with a reduction of the risk of total and cardiovascular mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
(9 reference statements)
3
17
0
1
Order By: Relevance
“…Other studies reported lack of association between warfarin use and mortality likely because warfarin use was parameterized as a time‐fixed exposure, potentially introducing misclassification. As Genovesi et al pointed out, it is necessary to consider the actual time of warfarin intake in the analysis for the protective effect of the drug to become evident . We accounted for the fact that warfarin users often discontinue or change their treatment at a high rate by defining warfarin use as a time‐varying variable.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies reported lack of association between warfarin use and mortality likely because warfarin use was parameterized as a time‐fixed exposure, potentially introducing misclassification. As Genovesi et al pointed out, it is necessary to consider the actual time of warfarin intake in the analysis for the protective effect of the drug to become evident . We accounted for the fact that warfarin users often discontinue or change their treatment at a high rate by defining warfarin use as a time‐varying variable.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, our findings may be more generalizable to older adults undergoing dialysis who may have complex oral anticoagulation treatment. While our study did not investigate the cause of death, other reports suggested that the reduction in mortality may be due to a reduction in cardiovascular death rather than stroke death …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently published systematic reviews and observational studies suggest that warfarin is not beneficial in reducing stroke risk but is associated with increased bleeding risk in patients with AF undergoing dialysis [1417], especially among older dialysis patients [18, 19]. However, there was some emerging evidence suggesting that warfarin use is associated with a reduction in mortality, even in the absence of a reduction in stroke incidence [2024]. …”
Section: Introductionmentioning
confidence: 99%
“…Although a recent meta-analysis finds that VKAs do not reduce stroke rate in ESRD patients on replacement therapy, and is associated with a 30% increase in major bleeding [13], some recent studies suggest that these patients with AF when treated with VKAs have a better survival compared with patients not anticoagulated. Warfarin benefit seems to be particularly evident in patients taking VKAs without interruption, and with an INR kept in therapeutic range [33,34]. In case of DE overdose, and in case of life-threatening bleeding, haemodialysis can be used to reduce DE level, and stop bleeding [32].…”
Section: Using Direct Oral Anticoagulants In Patients With Chronic Kimentioning
confidence: 99%